ANTIOXIDANT CAPACITY OF MECONIUM IN NEWBORNS OF MOTHERS WITH PREECLAMPSIA - Suarez Cunza, Silvia (2015)
OBJETIVE: To determine the antioxidant capacity of meconium in newborns from preeclamptic women. MATERIALS AND METHODS: the first meconium of newborn normal pregnancy and preeclampsia (PE) was obtained slight, and twelve hours before he was taken to lyophilization, for an average of seven hours. RESULTS: A total of 60 pregnancies, human meconium was found to have high capacity to scavenge free radicals, 19.0 ± 64.5% in normal pregnancies and 24.0 ± 43.6% in the PE group, which It gives a significant difference (a <0.01). Regarding the content of glutathione, the results were 15.6 ± 3.8 pmol / g and 10.8 ± 3.2 pmol / g meconium for the normal group and preeclampsia, respectively; and, with respect to bilirubin, 26.9 ± 12.3 in the normal group and 20.1 ± 7.0 in the group with PE. CONCLUSION: The meconium seems to be a powerful antioxidant, but this capacity decreases in pregnancies complicated by preeclampsia.